In vivo 4D imaging of the human lower airway using anatomical optical coherence tomography - McLaughlin, R.; Williamson, J.; Curatolo, A.; Baker, V.; Hillman, D.; Eastwood, Peter; Sampson, D. (2009)
Anatomical optical coherence tomography (aOCT) is a long-range, fibre-optic endoscopic imaging modality capable of quantifying the size and shape of the human airway lumen. This paper presents the first application of respiratory gating to 3D aOCT volumetric data. A sequence of time-gated data volumes are generated, characterising the dynamic behaviour of a segment of the lower airway over an averaged respiratory cycle. The technique is demonstrated on in vivo data acquired from three human subjects. © 2009 SPIE.